A acetabularização como fator protetor na artropatia do manguito rotator - Esteves, Leonardo Roure [UNIFESP] (2019)
Objective: Identify in cases of patients with a diagnosis of rotator cuff arthropathy if the shoulders with acetabularization have better functional results. Methods: In this work, a descriptive cross sectional study was carried out at Deltamed Clinic, from December 2016 to January 2019. The sample consisted of 65 shoulders of 56, 47 female and 9 male, aged between 60 and 88 years who were diagnosed by means of anteroposterior radiographs of the shoulder and magnetic resonance imaging of the shoulder with rotator cuff arthropathy (RCA). Of these 56 subjects, 9 individuals had bilateral involvement, thus totaling the 65 shoulders of this sample. All patients completed and signed the informed consent form, after a thorough explanation of the study. It was possible to identify and classify the respective types and stages of RCA and to divide into groups according to Seebauer and Hamada classifications. To characterize the tendon lesion (supraspinatus, infraspinatus, subscapular and long biceps cord), and classify for Goutallier'sfatty infiltration of the muscle a magnetic resonance imaging (MRI) of the shoulder was performed. The range of motion of the shoulder (anterior elevation, lateral rotation and medial rotation) was measured; to evaluate the function of the patients' shoulder, the Constant- Murley score (CMS-BR), validated for Portuguese language, was used. For the statistical analysis, parametric tests were used for the quantitative and continuous variables and, for inferencial analysis, the ANOVA tests and the multiple post hoc comparison of Tuckey were used; the significance level adopted was 0.05 and 95% confidence intervals. Results: The best functional results were observed in patients whose shoulders presented acetabularization. Regarding the range of motion, according to the Seebauer classification, type A patients presented the best results; statistically significant differences were found regarding anterior elevation and medial rotation between types A and B (p <0.05). Regarding lateral rotation, types A and B did not present statistically significant differences. In the Constant score there was a statistically significant difference between patients types A and B (p <0.05); the best results were observed in types 1A and 2A. According to Hamada's classification, with regard to range of motion and with respect to anterior elevation and medial rotation, stages 3, 2 and 1 presented better results when compared with stages 4A, 4B and 5 and, it was found a statistically significant difference between stages 3 and 5 (p <0.05). There was no statistically significant difference between the Hamada groups according the lateral rotation. The Constant score, according to Hamada's classification, showed that better results are observed in stages 3, 2 and 1 and there was a statistical difference between stages 3 and 5. Considering the functional results of the shoulder according to the Seebauer and Hamada classifications the best results were found in the groups of Seebauer 1A and Hamada 3, where there is acetabularization. Conclusion: Acetabularization has been shown to be associated with cases with better functional results in the shoulders with RCA.